2021
DOI: 10.3390/ijerph182412963
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Clinical and Radiologic Data Regarding Zygomatic Implant Rehabilitation with a Long-Term Follow-Up

Abstract: Background: Zygomatic implants have been introduced to rehabilitate edentulous patients with severely atrophic maxillae. Their use has been reported by several studies, describing high overall survival rates at medium–long follow-up. The aim of this study was to retrospectively analyze if a few patient-related and implant-related features are correlated with implant success or the onset of complications. Materials and methods: Data of patients treated with zygomatic implants between May 2005 and November 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…2 ). The lowest survival was 76.1% [95% CI 64.1; 85.7] survival at 141.6 months [ 30 ], whilst 3 studies reported 100% survival at 60, 85, and 101 months, respectively [ 13 , 18 , 27 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…2 ). The lowest survival was 76.1% [95% CI 64.1; 85.7] survival at 141.6 months [ 30 ], whilst 3 studies reported 100% survival at 60, 85, and 101 months, respectively [ 13 , 18 , 27 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Even if dental implants may significantly contribute to restore an adequate overall functionality, fixtures of standard dimensions cannot be used in most of the abovementioned cases, for lack of sufficient bone levels [ 2 ]. Several options have been developed over the years to correct deficient edentulous ridges, including short or reduced diameter dental implants [ 3 , 4 ]; tilted dental implants [ 5 ]; zygoma implants [ 6 ]; bone splitting/expansion of narrow ridges [ 7 ]; alveolar distraction osteogenesis [ 8 ]; guided bone regeneration [ 9 ]; and Le Fort I osteotomy with inter-positional bone grafts [ 2 , 10 ] (in cases of large sagittal discrepancy between the jaws and when implant inclination is too unfavorable). In this proposal, one of the most frequently employed procedures is represented by the reconstruction of alveolar defects with autogenous bone grafts, harvested from intraoral or extraoral sites: this modality of treatment was found to be a reliable means to correct both moderate and severe alveolar bone deficiencies of partially or totally edentulous patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zygomatic implants have demonstrated their effectiveness as a viable solution in addressing the challenges of managing atrophic edentulous maxilla [3][4][5][6] and maxillectomy defects [7]. Brånemark introduced these implants to cater to patients requiring prosthetic rehabilitation due to extensive maxillary defects resulting from tumor resections, trauma, and congenital issues [8].…”
Section: Introductionmentioning
confidence: 99%